INFLUENCE OF SODIUM GLUTAMATE, BUBBLING N2- GAS AND SUPERFICIAL AERATION ON TETANUS TOXIN PRODUCTION IN Clostridium tetani CULTURES - Gutiérrez, I.; Laboratorio de Tétanos, Instituto Nacional de Salud. (2005)
The influence of sodium glutamate as a supplement to Latham Mueller medium, while using bubbling nitrogen flow as an anaerobic agent and superficial aeration as an inducer of cell lysis and as a mechanism for the haulage of gases in the fermentation processes was evaluated. Using the Clostridium tetani Massachusetts’s strain, several five (5) liter batch fermentations were carried out for tetanus toxin production under the following conditions: Latham Mueller medium, with or without sodium glutamate, nitrogen flow and superficial aeration. The results demonstrated that the addition of sodium glutamate (2.5 g/l), combined with a bubbling nitrogen flow (0.33 l/min) and superficial aeration (0.33 l/min), produced asignificant increase in cell concentrations, repressing the tetanus toxin formation; while the gas flow (nitrogen and superficial aeration) without sodium glutamate improved the toxin production by approximately 49%, providing conditions for the following outcomes: a maximum toxin level of 73 Lf/ml; a toxin formation rate of 1844.0 Lf/l.h; and, an over-all productivity of 833.5 Lf/l.h.